New form of generlized closed sets via neutrosophic topologicl spaces - et. al., BinoyBalan eK, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Florentin eSmarandache egeneralized ethe eintuitionistic efuzzy esets eto eNeutrosophic eset etheory ein e1998 eas ea enew ebranch eof ephilosophy. eA.A. eSalama eintroduced ethe econcept eof eNeutrosophic etopological espaces eby eusing ethe eNeutrosophic ecrisp esets. eIn ethis epaper, ewe eintroduce eand estudy ea enew eclass eof eNeutrosophic egeneralized eset, enamely eNeutrsophic epre egeneralized eregular eα- eclosed eset ein eNeutrosophic etopological espaces. eSome einteresting epropositions ebased eon ethis eset eare eintroduced eand established ewith esuitable examples eand etheir eproperties eare ealso ediscussed.